2021
DOI: 10.1186/s40359-021-00688-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety and stress during the COVID-19 pandemic: a cross-sectional study among Palestinian students (10–18 years)

Abstract: Background The COVID-19 pandemic considers a threat to students’ well-being and mental health. The current descriptive cross-sectional study aims to identify psychological distress among school students during the lockdown period. Methods This study was carried out in a sample of 420 primary and secondary school students from June 10 to July 13, 2020, in the Gaza Strip in Palestine. Data was collected using an online questionnaire that included inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 70 publications
7
37
2
Order By: Relevance
“…People tend to suffer from sadness, stress, and anxiety during a health crisis, due to the panic of being infected with the disease [ 5 , 6 , 7 , 8 ]. People who suffer from diseases that do not have a cure or immunization will experience worry, tension, depression, and anxiety [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…People tend to suffer from sadness, stress, and anxiety during a health crisis, due to the panic of being infected with the disease [ 5 , 6 , 7 , 8 ]. People who suffer from diseases that do not have a cure or immunization will experience worry, tension, depression, and anxiety [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the contemporary world, the COVID-19 pandemic appeared as the most devastating turmoil among students belonging to socially disadvantaged countries since they have more stressors and are more vulnerable to stress due to a lack of mental health facilities 43 44. Further, sudden academic transition prompts a sense of insecurity about their learning journey that triggers appalling consequences on their well-being and calls for pandemic preparedness measures 19 45.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stress among University of Nizwa students in Oman reported that 82.5% were experiencing medium stress, while 14.4% experienced raised stress during COVID-19 e-learning [41]. A sample of 420 primary and secondary school students in Palestine showed that 35.7% experienced moderate to severe stress levels [42]. University students are primarily acknowledged as a vulnerable population; therefore, the radical shift in education affects students regardless of their socio-economic status.…”
Section: Plos Onementioning
confidence: 99%